The next frontier : national development, political change, and the death penalty in Asia - Johnson, David T. (David Ted), 1960-; Zimring, Franklin E. (Oxford : Oxford University Press, 2009)
The authors review the prospects for abolition of the death penalty throughout Asia in a series of authoritative case studies and investigate the continuities and limits between European abolition and attendant human rights perspectives and the culture, government, and policy of Asian nations.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Capital punishment -- Asia; Capital punishment -- Asia -- Case studies